Proposta de teste incremental baseado na percepção subjetiva de esforço para determinação de limiares metabólicos e parâmetros mecânicos do nado livre - Lima, Manoel Carlos Spiguel; Balikian Jr., Pedro [UNESP]; Gobatto, Cláudio Alexandre [UNESP]; Garcia Jr., Jair Rodrigues; Ribeiro, Luiz Fernando Paulino (My University, 2006)
The Rating of Perceived Exertion (RPE) is non-invasively determined and used together with lactacidemic analysis as indicator of intensity during incremental test. In field, especially in swimming, due to the difficulty of sample collection, alternative protocols have been used to estimate the anaerobic threshold. Thus, the study aims were: to prescribe one incremental test based on Borg's scale; to estimate metabolic thresholds determined through analysis lactate methods [settling bi-segmented (VLT), fixed concentration-3.5 mM (V3.5mM) and maximal distance (V Dmáx)]; to relate the RPE attributed in each stage with a heart rate (HR) and swimming mechanical parameters [stroke rate (SR), and stroke length (SL)]; to analyze the utilization of the Borg's scale in regularity of velocity increment in test and relate the metabolic thresholds with the critical velocity (CV). Twelve swimmers (16.4 ± 1.3 years old) were subjected to two maximal efforts (200 and 400 meters), the data was used to determine the CV, velocity in 400 meters (V400m) and critical stroke rate (CSR); and one incremental test with an initial intensity based in RPE, respectively, 9, 11, 13, 15 and 17; the HR, lactacidemia ([Lac]) and the times of four cycles strokes and the distances of 20 m and 50 m, were monitored in all stages. Subsequently, the velocity of the SR, SL, VLT, V3.5mM and VDmáx stages were calculated. ANOVA and correlation of Pearson were used to analyze the results. Significant differences were not found among VC, VDmáx and VLT, however the V3,5mM was lower than all velocities (P < 0.05). Significant relationships (P < 0.05) were found among VC versus V400m, VDmáx, V3.5mM; V400m versus V3.5mM and V Dmáx; VDmáx versus VLL; in incremental test among the RPE versus velocity, [Lac], HR, SR and SL (P < 0.05). Our conclusion was that RPE is a reliable tool for velocity control of stages during incremental test in swimming.
Incremental test proposal based on the rating of perceived exertion to determine metabolic thresholds and mechanical parameters of free style
Keywords: Blood lactate concentration; Heart rate; Stroke length; Stroke rate